Skeletal Muscle in Hypoxia and Inflammation: Insights on the COVID-19 Pandemic - Di Girolamo, Filippo G.; Fiotti, Nicola; Sisto, Ugo G.; Nunnari, Alessio; Colla, Stefano; Mearelli, Filippo; Vinci, Pierandrea; Schincariol, Paolo; Biolo, Gianni (Frontiers in Nutrition, 2022)
SARS-CoV-2 infection is often associated with severe inflammation, oxidative stress, hypoxia and impaired physical activity. These factors all together contribute to muscle wasting and fatigue. In addition, there is evidence of a direct SARS-CoV-2 viral infiltration into skeletal muscle. Aging is often characterized by sarcopenia or sarcopenic obesity These conditions are risk factors for severe acute COVID-19 and long-COVID-19 syndrome. From these observations we may predict a strong association between COVID-19 and decreased muscle mass and functions. While the relationship between physical inactivity, chronic inflammation, oxidative stress and muscle dysfunction is well known, the effects on muscle mass of COVID-19-related hypoxemia are inadequately investigated. The aim of this review is to highlight metabolic, immunity-related and redox biomarkers potentially affected by reduced oxygen availability and / or muscle fatigue in order to shed light on the negative impact of COVID-19 on muscle mass and function. Possible countermeasures are also reviewed.